Quantitation and sensory properties of three newly identified pyroglutamyl oligopeptides in sake. Issue 2 (1st February 2019) - Hashizume, Katsumi; Ito, Toshihiko; Nagae, Yusuke; Tokiwano, Tetsuo
ABSTRACT: Three new peptides: (pGlu)L-ethyl, (pGlu)LFGP-ethyl and (pGlu)LFNP-ethyl, were identified in the search for pyroglutamyl oligopeptide ethyl esters in sake. The ethyl esterified peptides in sake were quantitated using stable isotope dilution analysis and additional quantitation of (pGlu)L was performed using an external standard method. The concentrations of (pGlu)L-ethyl and (pGlu)L in 33 commercial sake samples ranged from 0.16 to 1.57 mg/L and 1.49 to 7.55 mg/L, respectively. The sensory properties of the pyroglutamyl oligopeptide ethyl esters and corresponding non-esterified peptides were examined: the estimated difference threshold of (pGlu)L (2.0 mg/L) and (pGlu)L-ethyl (0.267 mg/L) was exceeded in 32 and 26 samples, respectively. Estimated thresholds of (pGlu)LFGP-ethyl and (pGlu)LFNP-ethyl were often lower than the levels in quantitated sake samples. The sensory effects of these pyroglutamyl dipeptides on a model sake quality may be negative because of their unpleasant taste, however, (pGlu)LFNP-ethyl may be positive because of its mild taste. Graphical abstract: : Three new pyroglutamyl oligopeptides ethyl esters were identified in sake. Their quantitated levels often exceeded the estimated threshold values.